2017
DOI: 10.1021/acs.oprd.7b00145
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Polymer Additive To Enhance Impurity Rejection in the Crystallization of a Pharmaceutical Compound

Abstract: The control of impurity content in active pharmaceutical ingredients is of utmost importance for the pharmaceutical industry. While crystallization is oftentimes used as an efficient and cost-effective means of achieving this purification, structurally similar impurities can be very difficult to separate via crystallization. The impact of nonadsorbing polymers on the crystallization of the compound of interest can be leveraged to enhance the purification of pharmaceutical molecules. Here we discuss a case stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Copper/poly(ethylene oxide)/low density polyethylene composite [33] Guar gum, pectin, κ-carrageenan, gelatin, polyvinylpyrrolidone Thiamine chloride hydrochloride [34] Poly(acrylic acid), poly(N-vinyl pyrrolidone), poly(4-vinylphenol) Ibuprofen [46] Polymers functionalized from a parent batch of poly(chloromethylstyrene-co-styrene) Nabumetone [47] Functionalized poly(N-hydroxyethyl acrylamide) Ethenzamide [48] Hydroxypropylmethyl cellulose Felodipine [49] Alginate Lovastatin, indomethacin, itraconazole [50] Hydroxypropyl methylcellulose and methylcellulose polymers Griseofulvin [51] Hydroxypropyl methylcellulose, polyvinylpyrrolidone), Eudragit L-100 Griseofulvin, danazol [52] Different polymers of vinylpyrrolidone and a copolymer of vinylpyrrolidone and vinylacetate Sixteen drugs of different chemical nature [53] Polyvinylpyrrolidone Celecoxib [55,56] Nylon 6/6, polypropylene, polyvinylchloride paracetamol [59] Polyvinylpyrrolidone, hydroxypropyl methyl cellulose, Kollidone VA64 Indomethacin [65] Hydroxypropyl methylcellulose, polyvinylpyrrolidone Naproxen [68] Polyvinylpyrrolidone Naproxen [69] Polyvinylpyrrolidone Carvedilol [70] Poly(vinyl alcohol), polyethylene glycol Nitrendipine [71] Poly(ethylene imine) Eprosartan [75] Poly(N-isopropyl acrylamide) Nitrofurantoin [76] Hydroxypropylmethyl cellulose, copovidone Complex impurity [77] Polyvinylpolypyrrolidone K30 and K90, polyethyleneglycol 6000, polyethylene-polypropylene glycol 188 Pioglitazone [80] Poly(ethylene glycol)-block-poly(lactic acid) Tolazamide [81] Poly(ethylene glycol), poly(ethylene oxide)-poly(propylene oxide) triblock, hydroxypropyl cellulose, poly(acrylic acid), poly(ethylene imine), elastin-like peptide, chitosan…”
Section: Crystal Surface Screening/nucleation Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper/poly(ethylene oxide)/low density polyethylene composite [33] Guar gum, pectin, κ-carrageenan, gelatin, polyvinylpyrrolidone Thiamine chloride hydrochloride [34] Poly(acrylic acid), poly(N-vinyl pyrrolidone), poly(4-vinylphenol) Ibuprofen [46] Polymers functionalized from a parent batch of poly(chloromethylstyrene-co-styrene) Nabumetone [47] Functionalized poly(N-hydroxyethyl acrylamide) Ethenzamide [48] Hydroxypropylmethyl cellulose Felodipine [49] Alginate Lovastatin, indomethacin, itraconazole [50] Hydroxypropyl methylcellulose and methylcellulose polymers Griseofulvin [51] Hydroxypropyl methylcellulose, polyvinylpyrrolidone), Eudragit L-100 Griseofulvin, danazol [52] Different polymers of vinylpyrrolidone and a copolymer of vinylpyrrolidone and vinylacetate Sixteen drugs of different chemical nature [53] Polyvinylpyrrolidone Celecoxib [55,56] Nylon 6/6, polypropylene, polyvinylchloride paracetamol [59] Polyvinylpyrrolidone, hydroxypropyl methyl cellulose, Kollidone VA64 Indomethacin [65] Hydroxypropyl methylcellulose, polyvinylpyrrolidone Naproxen [68] Polyvinylpyrrolidone Naproxen [69] Polyvinylpyrrolidone Carvedilol [70] Poly(vinyl alcohol), polyethylene glycol Nitrendipine [71] Poly(ethylene imine) Eprosartan [75] Poly(N-isopropyl acrylamide) Nitrofurantoin [76] Hydroxypropylmethyl cellulose, copovidone Complex impurity [77] Polyvinylpolypyrrolidone K30 and K90, polyethyleneglycol 6000, polyethylene-polypropylene glycol 188 Pioglitazone [80] Poly(ethylene glycol)-block-poly(lactic acid) Tolazamide [81] Poly(ethylene glycol), poly(ethylene oxide)-poly(propylene oxide) triblock, hydroxypropyl cellulose, poly(acrylic acid), poly(ethylene imine), elastin-like peptide, chitosan…”
Section: Crystal Surface Screening/nucleation Inhibitionmentioning
confidence: 99%
“…They found that slower nucleation and growth rates of the crystals were observed regardless of the molecular weight or stereoconfiguration of the PNIPAM. Czyzewski et al in their experiments used a polymer additive such as HPMC or PVP to successfully reject impurity of sulfonamide based drug which cannot be removed via conventional crystallization [ 77 ]. Frank et al using pyrazinamide (an antibiotic used to treat tuberculosis) and hydrochlorothiazide (diuretic used to treat blood hypertension and edema) as model pharmaceutical, demonstrated that the rate of crystallization can be controlled by polymer solubility present in the solution [ 78 ].…”
Section: Present and Future Perspectives Of Applications Of Crystallization Phenomena In The Presence Of Polymersmentioning
confidence: 99%
“…81,82 In one case, the ability to impact API and not impurity supersaturation relief kinetics allowed for greater impurity rejection. 83 In another clear example of the impact of changes in physical properties, morphology modification brought about by crystallization in the presence of hydroxypropyl cellulose polymer yielded improved compactability of the API. 8,84 Another study showed levels of polymer of 0. resulted in composite particles with improved API physical properties, while higher levels of polymer (∼9−12 wt %) stabilized a kinetic crystalline phase.…”
Section: ■ Routes To Generate Co-processed Apimentioning
confidence: 99%
“…The use of low levels (generally <5 wt %, and often <0.1 wt %) of carefully selected, pharmaceutically acceptable additives to alter conventional crystallization processes has been explored to improve API physical properties during crystallization. Pharmaceutically acceptable additives have demonstrated the ability to alter API crystal form, ,, morphology, , surface features, nucleation, , and supersaturation relief/growth rate. , In one case, the ability to impact API and not impurity supersaturation relief kinetics allowed for greater impurity rejection . In another clear example of the impact of changes in physical properties, morphology modification brought about by crystallization in the presence of hydroxypropyl cellulose polymer yielded improved compactability of the API. , Another study showed levels of polymer of 0.4–5 wt % altered morphology and resulted in composite particles with improved API physical properties, while higher levels of polymer (∼9–12 wt %) stabilized a kinetic crystalline phase .…”
Section: Routes To Generate Co-processed Apimentioning
confidence: 99%